Mejoramiento de la gestión integral de los residuos sólidos en el distrito de Yantalo - Chávez Chávez, Betzabeth (2014)
This thesis project was implemented in the Yantalo District, specifically in the Yantalo City, whose specific objectives were:To determine the generation and physical composition of the so lid municipal residues of Yantalo District, to diagnose the current situation of the Integral Management of the solid residues of Yantalo District, to determine the environmental impacts of the managing of the so lid municipal residues in Yantalo district and with the only intention of contributing to the solution of sorne social problems of collective interest, since it is the case of the inadequate managing of the solid municipal residues of Yantalo District, Moyobamba Province, San MartinRegion. This research has been allowed us to reach the conclusion: • That the GPC obtained is 0.54 kg/hab/day, which we obtained a generation of 1,802 Tn/day that generates the Yantalo city; in the case ofthe composition is obtained that the largest percentage 82,133 % is organic matter, 10.84% is inert material and the earth and in little proportion 7.02% other waste (plastic bottles, glass, paper, etc). • It was determined that the Integrated Solid Waste Management of the District Municipality ofYantalo is not adequate. • Identified the main environmental impacts identified in the Y antalo District are: Damage to the landscape, soil and watercontamination, adverse effects in the wild flora and fauna; in health: a proliferation of pests and vectors, injuries to his hands and feet and disease incidence. • Was able to produce a plan of Solid Waste Management YantaloDistrict Municipality, which seeks to improve the integrated solid waste management of the YantaloDistrict Municipality. For this it could say that it has complied with the stated objectives, for what it is recommendec;l to get a copy to the Yantalo District Muriicipality to be implemented, and with this can be achieved for proper Integrated Solid Waste Management. Key words: Solid Waste Management; environmental impacts.